2015
DOI: 10.1177/1933719115570901
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of α1-Antitrypsin in Endometriosis-Like Grafts From a Mouse Model of Endometriosis

Abstract: Previous study indicated that bleeding into the peritoneum may accelerate inflammatory response in endometriosis-like grafts in mice. To identify changes in protein levels in the grafts from mice that underwent unilateral ovariectomy (uOVX), which causes bleeding from ovarian arteries and vein, the grafts were generated by injecting a suspension of human endometrial cells in BALB/c nude female mice, and protein profile changes were compared with non-uOVX control mice. The level of α1-antitrypsin (α1-AT) decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Sustained activation of ERK1/2 was also found to be involved in renal endothelial inflammation [ 42 ], myofibroblast differentiation, extracellular matrix production [ 43 ] and fibrosis [ 44 ] in the course of SSc. Interplay between PAR-1 and p70S6K was also demonstrated in animal models of neuronal ischemia [ 45 ] and endometriosis [ 46 ]. Corroborating our results, phosphorylation of p70S6K was also detected in the renal endothelium of patients with SRC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained activation of ERK1/2 was also found to be involved in renal endothelial inflammation [ 42 ], myofibroblast differentiation, extracellular matrix production [ 43 ] and fibrosis [ 44 ] in the course of SSc. Interplay between PAR-1 and p70S6K was also demonstrated in animal models of neuronal ischemia [ 45 ] and endometriosis [ 46 ]. Corroborating our results, phosphorylation of p70S6K was also detected in the renal endothelium of patients with SRC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, it has been proposed that the globular surface of hAAT may contain significant functional attributes. Indeed, it has been established that hAAT directly binds IL-8 ( 21 , 22 ), as well as to polymeric immunoglobulin receptor ( 23 ), gp96 ( 24 ), HSP70 ( 25 ), oxidized cholesterol within lipid rafts and serum lipids ( 26 29 ), HDL particles ( 30 32 ), and LRP1 receptor ( 33 ). Furthermore, certain activities that are attributed to hAAT appear to be reproducible in formulations that lack elastase inhibition as in the case of recombinant Fc-hAAT and truncated hAAT ( 26 , 34 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…In human placental tissue, A1AT may interact directly with HTRA1 [4,7] and suppress the inflammatory response [4,7]. The effect of A1AT knockdown (KD) or overexpression (OE) on the expression of HTRAs and the pro-inflammatory genes IL6 and CXCL8 was determined in HTR8/SVneo cells (Figure 1a,b).…”
Section: Alpha-1 Antitrypsin (A1at) Regulates the Expression Of Htra1 In An Extravillous Trophoblast Cell Linementioning
confidence: 99%
“…This serine protease inhibitor is present at high circulating concentrations in inflammatory diseases [3]. Previous studies have shown that a reduction of A1AT protein in endometriosis-like lesions exacerbates the inflammatory response in mice [4]. It has been shown that urinary A1AT may represent a marker of the severity of PE [5].…”
Section: Introductionmentioning
confidence: 99%